Overview [in Africa agriculture trade monitor 2019] - Bouët, Antoine; Odjo, Sunday P. (International Food Policy Research Institute, 2019)
This is the second annual Africa Agriculture Trade Monitor (AATM), a fl agship publication that is part of a collaborative initiative between the International Food Policy Research Institute (IFPRI) and the Technical Centre for Agricultural and Rural Cooperation (CTA). The reports assess emerging and long-term trends and drivers behind Africa’s trade in agricultural products— including global trade, intra-African trade, and trade within regional economic communities (RECs).